The cycle of form and function in cardiac valvulogenesis - Stephanie E. Lindsey; Jonathan T. Butcher (Global Cardiology Science & Practice, 2011)
The formation and remodeling of the embryonic valves is a complex and dynamic process that occurs within a constantly changing hemodynamic environment. Defects in embryonic and fetal valve remodeling are the leading cause of congenital heart defects, yet very little is known about how fibrous leaflet tissue is created from amorphous gelatinous masses called cushions. Microenvironmental cues such as mechanical forces and extracellular matrix composition play major roles in cell differentiation, but almost all research efforts in valvulogenesis center around genetics and molecular approaches. This review summarizes what is known about the dynamic mechanical and extracellular matrix microenvironment of the atrioventricular and semilunar valves during embryonic development and their possible guidance roles. A variety of new computational tools and sophisticated experimental techniques are progressing that enable precise microenvironmental alterations that are critical to complement genetic gain and loss of function approaches. Studies at the interface of mechanical and genetic signaling in embryonic valvulogenesis will likely pay significant dividends, not only in terms of increasing our mechanistic understanding, but also lead to the development of novel therapeutic strategies for patients with congenital valve abnormalities.